Toxicity screening of Diclofenac, Propranolol, Sertraline and Simvastatin using Danio rerio and Paracentrotus lividus embryo bioassays - Ribeiro, Sílvia (2016)
Early life-stage bioassays have been used as an alternative to short-term adult toxicity tests since they are cost-effective. A single couple can produce hundreds or thousands of embryos and hence can be used as a simple high-throughput approach in toxicity studies. In the present study, zebrafish and sea urchin embryo bioassays were used to test the toxicity of four pharmaceuticals belonging to different therapeutic classes: diclofenac, propranolol, simvastatin and sertraline. Simvastatin was the most toxic tested compound for zebrafish embryo, followed by diclofenac. Sertraline was the most toxic drug to sea urchin embryos, inducing development abnormalities at the ng/L range. Overall, our results highlight the potential of sea urchin embryo bioassay as a promising and sensitive approach for the high-throughput methods to test the toxicity of new chemicals, including pharmaceuticals, and identify several drugs that should go through more detailed toxicity assays.